The Molecular Effect of Curcumin Subsidized by Radiation on HepG2 cell lines (Journal of Nuclear Technology in Applied Science, 2018)
Cancer is a major health problem around the world. Cancer treat ment depends on radiation therapy sometimes in combination with che motherapy or hormonal therapy. The treatment of cancer with radiation  and chemotherapy cause several unwanted harmful side effects. Turmeric  (Curcuma longa), is a type of herb widely used as a spice. Recent re searches have shown that curcumin, the active component of turmeric  possesses anticancer properties. This study aimed to evaluate the effect  of γ-radiation and curcumin each of them alone or combined on HepG2  cell line proliferation, p53, Her2/neu, and MMP9 gene expression, and total antioxidant capacity. HepG2 cells were exposed to γ-radiation (R), or treated with different concentrations of curcumin alone or combined  with each other. The cell viability was examined by MTT assay. Gene ex pression of p53, Her2/neu, and MMP9 were evaluated by using real-time  QPCR. The total antioxidant capacity (TAC) was also measured. Cur cumin or R alone or combined decreased cell viability and induced cell  death in a dose-and time-dependent manner when compared to untreated  group. Curcumin and R induced p53 gene expression, while reduced  Her2/neu, and MMP9 expression. Furthermore, the TAC was decreased  in the treated groups compared to the untreated. Conclusion: Curcumin  can sensitize HepG2 cells to radiation and would potentiate the effect of  radiotherapy in cancer..
Keywords: Curcumin; Hepatocellular Carcinoma; Gamma Radiation; p53; Her2/ neu; MMP9